The Effect of Financing Decisions, Investment Decisions, and Asset Manage-ment Decisions on Company Value with Dividend Policy as Moderating Varia-ble in Go Public Companies in Indonesia - Ira Wikartika; Kiky Asmara (Future Science, 2020)
Competition in the highly competitive business world demands the ability of company managers to implement business strategies appropriately so that company goals can be achieved. A good company's financial performance will have an impact on increasing the value of a company. This increase in company value is a positive signal that will attract investors to invest their funds in the company in the hope that they will get dividends. The purpose of this study was to determine the effect of funding decisions on firm value, the effect of investment decisions on firm value, the effect of asset management decisions on firm value, dividend policy in moderating the effect of funding decisions on firm value, dividend policy in moderating the effect of investment decisions on firm value, dividend policy in moderating the effect of asset management decisions on firm value. The research method used is a quantitative method with multiple linear regression analysis techniques. The study population uses publicly-traded companies on the Indonesian stock exchange. The research sample used companies included in the LQ45 index on the IDX during 2016-2018 as many as 34 companies. Sampling was carried out using non-random sampling techniques, with purposive sampling method, namely sampling based on the subjective considerations of the researcher where there are conditions that must be met by the sample. Based on the research results, it can be concluded that funding decisions, investment decisions, and asset management decisions affect firm value. Dividend policy is not able to moderate the interaction between funding decisions and asset management with firm value but can moderate the interaction between investment decisions and firm value.